A packaging aging-resistant PETG shrink film for protecting thin-film solar cells and a preparation method thereof

By adopting a PETG shrink film with a three-layer structure of A/B/A, combined with NPG modified PET and functional masterbatch, as well as a combination of PET, PETG, antioxidant and light stabilizer, the problem of insufficient aging resistance of existing packaging materials is solved, and thin-film solar cell packaging materials with high transparency, light transmittance and aging resistance are achieved.

CN116100898BActive Publication Date: 2025-03-11HENAN DAXINYUAN NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211107099.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-13
Publication Date
2025-03-11
Estimated Expiration
2042-09-13

AI Technical Summary

Technical Problem

Existing thin-film solar cell packaging materials are susceptible to moisture and oxygen during outdoor use, resulting in a shortening of battery life and insufficient transparency, sunlight transmittance and aging resistance of the material.

Method used

A PETG shrink film with three-layer structure of A/B/A, layer A is composed of NPG modified PET and functional masterbatch, and layer B contains PET, PETG, antioxidant and light stabilizer. It is prepared by a bidirectional tensile process to improve the mechanical strength and transparency of the film.

Benefits of technology

It significantly improves the transparency, light transmittance and aging resistance of the film, extends the service life of the battery, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116100898B_ABST
    Figure CN116100898B_ABST
Patent Text Reader

Abstract

The present invention discloses an aging-resistant PETG shrink film for protecting thin-film solar cells, wherein the shrink film layer structure is a three-layer structure of A / B / A; wherein the raw materials of the A layer include PET modified with NPG and a functional masterbatch; and the raw materials of the B layer include PET, PETG, an antioxidant and a light stabilizer. The present invention effectively reduces the production cost while ensuring the efficacy, and the surface layer of the film has good printability and heat-sealing properties, while also achieving the characteristics of high light transmittance, low haze and high transparency of the film, and improving durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of heat-sealing film preparation, and in particular relates to an encapsulating aging-resistant PETG shrink film for protecting thin-film solar cells and a preparation method thereof. Background Art

[0002] Thin-film solar cells are new photovoltaic devices that can alleviate the energy crisis. Thin-film solar cells can be manufactured using low-cost ceramics, graphite, metal sheets and other materials as substrates. The thickness of the film that can generate voltage only needs to be a few microns, and the current conversion efficiency can reach up to 13%. In addition to being flat, thin-film solar cells can also be made into non-planar structures because of their flexibility. They have a wide range of applications and can be combined with buildings or become part of the building. However, during outdoor use, they are inevitably affected by the combined effects of moisture and oxygen in the air, which causes the battery life to decrease rapidly and has a short service life. Therefore, it is urgent to synthesize battery packaging materials with excellent performance to increase the battery life.

[0003] During transportation and use, solar cells need to be encapsulated on the outside. At the same time, in order to protect the cells from mechanical stress, exposure and moisture, the series-connected cells are embedded in a transparent encapsulation material, which can provide electrical insulation for the cells. However, at the same time, the encapsulation film is also required to have high transparency and high sunlight transmittance to improve the photoelectric conversion efficiency. This ensures that the cells do not react with water, oxygen, etc. during transportation and operation. Water and oxygen enter the cells and then react chemically with the battery absorption layer structure, reducing the battery's photoelectric conversion efficiency and even damaging the internal structure of the battery, causing the battery to fail in a short time.

[0004] Currently, most of the packaging materials reported in the literature are waterproof materials, which do not have shrinkage, have average packaging effects, and have poor aging resistance and short service life. Summary of the invention

[0005] The present invention aims to overcome the shortcomings of the prior art and provides an encapsulation aging-resistant PETG shrink film for protecting thin-film solar cells, which has good transparency, chemical tolerance, shrinkage and stress whitening resistance, and a preparation method thereof.

[0006] To this end, the present invention provides an encapsulation aging-resistant PETG shrink film for protecting thin-film solar cells, wherein the shrink film layer structure is an A / B / A three-layer structure; wherein the raw materials of the A layer include PET modified with NPG and a functional masterbatch; and the raw materials of the B layer include PET, PETG, an antioxidant and a light stabilizer.

[0007] The A layer contains the following components by mass percentage: NPG modified PET: functional masterbatch = 99.2~96.0%: 0.8~4.0%.

[0008] The B layer contains the following components by mass percentage: PETG: PA: antioxidant and light stabilizer = 48-69.4%: 30-50%: 0.6-2.0%.

[0009] The PETG is preferably SKYGREEN® S2012, Eastman GN071 or Eastman 0603.

[0010] The PA is preferably at least one of MXD6 and Grivory G21.

[0011] The antioxidant is preferably tris(2,4-di-tert-butylphenyl)phosphite and pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0012] The light stabilizer is preferably bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0013] The functional masterbatch is preferably at least one of silicon dioxide, talc, clay, kaolin and the like compounded with oleic acid amide and fenic acid amide.

[0014] The present invention also provides a method for preparing the above-mentioned encapsulation aging-resistant PETG shrink film for protecting thin-film solar cells, comprising the following steps:

[0015] (1) The raw materials are uniformly mixed in a planetary mixer according to the proportion and then dried, and melt-plasticized in corresponding extruders according to the mixing of the core layer and the surface layer;

[0016] (2) Setting the three-layer structure of ABA, the melt is extruded through the same die head with a temperature of 260-280°C, and the cast sheet is cooled and formed on a quenching roller;

[0017] (3) longitudinally stretching the cast sheet under the following conditions: preheating at 80-90°C, stretching the sheet at 80-100°C to a ratio of 1-2 times, and cooling the sheet at 40-60°C after longitudinal stretching;

[0018] (4) Performing a transverse stretching operation, the stretching conditions are: preheating at 90-110°C, stretching the film to a ratio of 3 to 4 times at 70-90°C, and cooling and shaping the film at 60-80°C after transverse stretching;

[0019] (5) Pulling and rolling to obtain an aging-resistant heat-retractable thin-film solar cell packaging film.

[0020] The thickness of the aging-resistant heat-shrinkable thin-film solar cell packaging film is preferably 30 to 100 μm.

[0021] The invention provides a convenient heat-seal shrinkable material, which does not require an additional complex synthesis or composite process. By adding a suitable antioxidant and a light-stabilizing compounding agent during the mixing and melt extrusion of ingredients, the synergistic effect of the two additives effectively improves the aging resistance of the film, and does not affect the color transmittance of the film; the adapted biaxial stretching process makes the film have a moderate orientation degree and crystallinity in the transverse and longitudinal directions, ensures the mechanical strength of the film, and improves the transparency, transmittance and aging resistance of the film; adding a PA component to the core layer effectively improves the barrier property of the film, and the good barrier property can maintain the chemical properties of solar cells in a warm and humid environment and prolong the working life; the good shrinkage performance of the film can optimize the packaging and bonding effect of the battery, reduce other additional process operations, and effectively reduce the production cost; the A layer of the film has heat-sealability, which is conducive to industrial production and improves the packaging efficiency; the multilayer films have similar polarities and thus have good adhesion, and are not prone to stratification.

[0022] The present invention has the following advantages and effects over the prior art:

[0023] The effect:

[0024] 1. The three-layer structure of the heat-sealable shrink film prepared by the method is a derivative of PET material, with similar chemical properties, similar polarity, strong adhesion between the layers, and no stratification problem. The addition of heat-seal layer and adhesive layer can be avoided, the difficulty of equipment operation is reduced, the composite process is reduced, and the thickness of the functional film is reduced, thereby reducing the production cost while ensuring the efficacy. At the same time, the surface layer of the film has good printability, and patterns, logos and other instructions can be printed on the film, effectively improving the packaging and printing effects;

[0025] 2. The three-layer co-extruded film prepared by the method mainly comprises a PET material with a high melt index modified by NPG, CHDM or NPG+CHDM monomers, which effectively reduces the crystallinity of the material and has good heat-sealing strength, is conducive to industrial production, improves packaging efficiency, and can ensure the sealing of the film during use;

[0026] 3. Since the battery is sensitive to humidity and oxygen, the water and oxygen in the environment react chemically with the battery absorption layer, causing the battery to fail in a short time. The addition of suitable PA components in the core layer greatly improves the water vapor barrier and oxygen barrier properties of the film, and improves the film's protective effect on battery drying and oxygen isolation.

[0027] 4. The film prepared by this process, due to the addition of suitable antioxidants and light stabilizers, has a synergistic effect between the antioxidants and the light stabilizers, which effectively improves the processing performance of the film. At the same time, the aging resistance of the film under light and in a hot and humid environment is significantly higher than that of ordinary PETG film or PETG film using only one of them, which improves the service life of the film, that is, the protection time for the battery, and enables the packaging film to maintain its characteristics such as mechanical properties and barrier properties for a longer period of time.

[0028] 5. The film prepared by this process has low crystallinity and excellent optical properties. The addition of functional masterbatch, while the selected antioxidants and light stabilizers have little effect on the color and transmittance of the product, ensuring the high transmittance, low haze and high transparency of the film.

[0029] 6. The film adopts a biaxial stretching process, which continues to stretch horizontally after longitudinal stretching, so that the film has a moderate degree of crystallization, increases the film's tensile strength and other mechanical properties, effectively improves the film's air and moisture barrier properties, and to a certain extent extends the molecular chain orientation, increasing the film's aging resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a structural schematic diagram of the present invention. Specific embodiments

[0031] The effects of the high-transparency heat shrinkable film of the present invention are studied below through specific examples.

[0032] Example 1

[0033] (1) Dry the raw materials modified PET (WS501Y, Huahong Chemical Fiber), PETG (SKYGREEN, S2012), and PA (MXD6) in a vacuum dryer to remove moisture;

[0034] (2) Various ABA three-layer structure films are prepared according to the composition ratio and preliminarily mixed in a mixer, wherein:

[0035] The A layer contains the following components by mass percentage: NPG modified PET (WS501Y, Huahong Chemical Fiber): functional masterbatch (1.6% anti-blocking agent SiO2 and 1.6% slip agent crodamide ER) = 96.8%: 3.2%;

[0036] The B layer comprises the following components by mass percentage: PETG (SKYGREEN, S2012): PA (MXD6): antioxidant (tris(2,4-di-tert-butylphenyl)phosphite: tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester = 4:1): light stabilizer (bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate) = 68%: 30%: 1.7%: 0.3%;

[0037] (3) The ingredients are uniformly mixed in a planetary mixer for a mixing time of not less than 1 h. The mixing temperature is controlled at 70 °C. The ingredients are fed into a twin-screw extruder for melting and plasticization. The screw diameter is selected to be 80 mm, the aspect ratio is 32, and the temperature is 275 °C.

[0038] (4) The ingredients are mixed according to the ABA structure, and three extruders are co-extruded on the same die head with a die head temperature of 272°C;

[0039] (5) For melt extrusion casting, the ratio of the linear speed of the quenching roller to the melt outflow speed is controlled to be less than or equal to 5, and the temperature of the quenching roller is controlled at 35℃±2℃.

[0040] (6) Using infrared heating to perform single-point stretching, the cast sheet is longitudinally stretched. The stretching conditions are: preheating at 85°C, and then stretching the sheet at 90°C to a ratio of 1.5 times. After longitudinal stretching, the sheet is cooled at 50°C to set the shape;

[0041] (7) The transverse stretching is carried out by oil heating. The stretching conditions are: preheating at 100°C, and then stretching the film at 80°C to a ratio of 3.5 times. After transverse stretching, the film is cooled and fixed at 75°C.

[0042] (8) Pulling and rolling to obtain an aging-resistant heat-retractable thin-film solar cell packaging film, wherein the thickness ratio of the A layer, the B layer and the A layer is 8:84:8.

[0043] Example 2

[0044] (1) Dry the raw materials modified PET (WS501Y, Huahong Chemical Fiber), PETG (SKYGREEN, S2012), and PA (MXD6) in a vacuum dryer to remove moisture;

[0045] (2) Various ABA three-layer structure films are prepared according to the composition ratio and preliminarily mixed in a mixer, wherein:

[0046] The A layer contains the following components by mass percentage: NPG modified PET (WS501Y, Huahong Chemical Fiber): functional masterbatch (1.1% anti-blocking agent SiO2 and 1.1% slip agent crodamide ER) = 97.8%: 2.2%;

[0047] The B layer comprises the following components by mass percentage: PETG (SKYGREEN, S2012): PA (MXD6): antioxidant (tris(2,4-di-tert-butylphenyl)phosphite: tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester = 4:1): light stabilizer (bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate) = 58%: 40%: 1.5%: 0.5%;

[0048] (3) The ingredients are uniformly mixed in a planetary mixer for a mixing time of not less than 1 h. The mixing temperature is controlled at 70 °C. The ingredients are fed into a twin-screw extruder for melting and plasticization. The screw diameter is selected to be 80 mm, the aspect ratio is 32, and the temperature is 275 °C.

[0049] (4) The ingredients are mixed according to the ABA structure, and three extruders are co-extruded on the same die head with a die head temperature of 272°C;

[0050] (5) For melt extrusion casting, the ratio of the linear speed of the quenching roller to the melt outflow speed is controlled to be less than or equal to 5, and the temperature of the quenching roller is controlled at 35℃±2℃.

[0051] (6) Using infrared heating to perform single-point stretching, the cast sheet is longitudinally stretched. The stretching conditions are: preheating at 85°C, and then stretching the sheet at 90°C to a ratio of 1.5 times. After longitudinal stretching, the sheet is cooled at 50°C to set the shape;

[0052] (7) The transverse stretching is carried out by oil heating. The stretching conditions are: preheating at 100°C, and then stretching the film at 80°C to a ratio of 3.5 times. After transverse stretching, the film is cooled and fixed at 75°C.

[0053] (8) Pulling and rolling to obtain an aging-resistant heat-retractable thin-film solar cell packaging film, wherein the thickness ratio of the A layer, the B layer and the A layer is 8:84:8.

[0054] Example 3

[0055] (1) Dry the raw materials modified PET (WS501Y, Huahong Chemical Fiber), PETG (SKYGREEN, S2012), and PA (MXD6) in a vacuum dryer to remove moisture;

[0056] (2) Various ABA three-layer structure films are prepared according to the composition ratio and preliminarily mixed in a mixer, wherein:

[0057] The A layer contains the following components by mass percentage: NPG modified PET (WS501Y, Huahong Chemical Fiber): functional masterbatch (0.6% anti-blocking agent SiO2 and 0.6% slip agent crodamide ER) = 98.8%: 1.2%;

[0058] The B layer comprises the following components by mass percentage: PETG (SKYGREEN, S2012): PA (MXD6): antioxidant (tris(2,4-di-tert-butylphenyl)phosphite: tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester = 4:1): light stabilizer (bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate) = 48%: 50%: 1.0%: 1.0%;

[0059] (3) The ingredients are uniformly mixed in a planetary mixer for a mixing time of not less than 1 h. The mixing temperature is controlled at 70 °C. The ingredients are fed into a twin-screw extruder for melting and plasticization. The screw diameter is selected to be 80 mm, the aspect ratio is 32, and the temperature is 275 °C.

[0060] (4) The ingredients are mixed according to the ABA structure, and three extruders are co-extruded on the same die head with a die head temperature of 272°C;

[0061] (5) For melt extrusion casting, the ratio of the linear speed of the quenching roller to the melt outflow speed is controlled to be less than or equal to 5, and the temperature of the quenching roller is controlled at 35℃±2℃.

[0062] (6) Using infrared heating to perform single-point stretching, the cast sheet is longitudinally stretched. The stretching conditions are: preheating at 85°C, and then stretching the sheet at 90°C to a ratio of 1.5 times. After longitudinal stretching, the sheet is cooled at 50°C to set the shape;

[0063] (7) The transverse stretching is carried out by oil heating. The stretching conditions are: preheating at 100°C, and then stretching the film at 80°C to a ratio of 3.5 times. After transverse stretching, the film is cooled and fixed at 75°C.

[0064] (8) Pulling and rolling to obtain an aging-resistant heat-retractable thin-film solar cell packaging film, wherein the thickness ratio of the A layer, the B layer and the A layer is 8:84:8.

[0065] Example 4

[0066] (1) Dry the raw materials modified PET (WS501Y, Huahong Chemical Fiber), PETG (SKYGREEN, S2012), and PA (MXD6) in a vacuum dryer to remove moisture;

[0067] (2) Various ABA three-layer structure films are prepared according to the composition ratio and preliminarily mixed in a mixer, wherein:

[0068] The A layer contains the following components by mass percentage: NPG modified PET (WS501Y, Huahong Chemical Fiber): functional masterbatch (1.6% anti-blocking agent SiO2 and 1.6% slip agent crodamide ER) = 96.0%: 4.0%;

[0069] The B layer comprises the following components by mass percentage: PETG (SKYGREEN, S2012): PA (MXD6): antioxidant (tris(2,4-di-tert-butylphenyl)phosphite: pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate=4:1): light stabilizer (bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate)=69.4%:30%:0.4%:0.2%;

[0070] (3) The ingredients are uniformly mixed in a planetary mixer for a mixing time of not less than 1 h. The mixing temperature is controlled at 70 °C. The ingredients are fed into a twin-screw extruder for melting and plasticization. The screw diameter is selected to be 80 mm, the aspect ratio is 32, and the temperature is 275 °C.

[0071] (4) The ingredients are mixed according to the ABA structure, and three extruders are co-extruded on the same die head with a die head temperature of 272°C;

[0072] (5) For melt extrusion casting, the ratio of the linear speed of the quenching roller to the melt outflow speed is controlled to be less than or equal to 5, and the temperature of the quenching roller is controlled at 35℃±2℃.

[0073] (6) Using infrared heating to perform single-point stretching, the cast sheet is longitudinally stretched. The stretching conditions are: preheating at 85°C, and then stretching the sheet at 90°C to a ratio of 1.5 times. After longitudinal stretching, the sheet is cooled at 50°C to set the shape;

[0074] (7) The transverse stretching is carried out by oil heating. The stretching conditions are: preheating at 100°C, and then stretching the film at 80°C to a ratio of 3.5 times. After transverse stretching, the film is cooled and fixed at 75°C.

[0075] (8) Pulling and rolling to obtain an aging-resistant heat-retractable thin-film solar cell packaging film, wherein the thickness ratio of the A layer, the B layer and the A layer is 8:84:8.

[0076] Example 5

[0077] (1) Dry the raw materials modified PET (WS501Y, Huahong Chemical Fiber), PETG (SKYGREEN, S2012), and PA (MXD6) in a vacuum dryer to remove moisture;

[0078] (2) Various ABA three-layer structure films are prepared according to the composition ratio and preliminarily mixed in a mixer, wherein:

[0079] The A layer contains the following components by mass percentage: NPG modified PET (WS501Y, Huahong Chemical Fiber): functional masterbatch (1.6% anti-blocking agent SiO2 and 1.6% slip agent crodamide ER) = 99.2%: 0.8%;

[0080] The B layer comprises the following components by mass percentage: PETG (SKYGREEN, S2012): PA (MXD6): antioxidant (tris(2,4-di-tert-butylphenyl)phosphite: tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester = 4:1): light stabilizer (bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate) = 49.4%: 50%: 0.3%: 0.3%;

[0081] (3) The ingredients are uniformly mixed in a planetary mixer for a mixing time of not less than 1 h. The mixing temperature is controlled at 70 °C. The ingredients are fed into a twin-screw extruder for melting and plasticization. The screw diameter is selected to be 80 mm, the aspect ratio is 32, and the temperature is 275 °C.

[0082] (4) The ingredients are mixed according to the ABA structure, and three extruders are co-extruded on the same die head with a die head temperature of 272°C;

[0083] (5) For melt extrusion casting, the ratio of the linear speed of the quenching roller to the melt outflow speed is controlled to be less than or equal to 5, and the temperature of the quenching roller is controlled at 35℃±2℃.

[0084] (6) Using infrared heating to perform single-point stretching, the cast sheet is longitudinally stretched. The stretching conditions are: preheating at 85°C, and then stretching the sheet at 90°C to a ratio of 1.5 times. After longitudinal stretching, the sheet is cooled at 50°C to set the shape;

[0085] (7) The transverse stretching is carried out by oil heating. The stretching conditions are: preheating at 100°C, and then stretching the film at 80°C to a ratio of 3.5 times. After transverse stretching, the film is cooled and fixed at 75°C.

[0086] (8) Pulling and rolling to obtain an aging-resistant heat-retractable thin-film solar cell packaging film, wherein the thickness ratio of the A layer, the B layer and the A layer is 8:84:8.

[0087] Comparative Example 1

[0088] In this embodiment, the NPG modified PET in the surface layer 1 and the surface layer 3 is prepared by (YH101, Yuanhong Polymer), and the other components and other layer components are the same as those in Example 2, and the preparation method is consistent with that in Example 2.

[0089] Comparative Example 2

[0090] In this embodiment, the core layer 2 contains the following components in percentage by mass: PA (MXD6): antioxidant (tris (2,4-di-tert-butylphenyl) phosphite: tetrakis [3- (3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester = 4:1): light stabilizer (bis (2,2,6,6-tetramethyl-4-piperidinyl) sebacate) = 98%: 1.5%: 0.5%; the other layer components are the same as those in Example 2, and the preparation method is consistent with that in Example 2.

[0091] Comparative Example 3

[0092] In this embodiment, the core layer 2 contains the following components in percentage by mass: PETG (SKYGREEN, S2012): antioxidant (tris(2,4-di-tert-butylphenyl)phosphite: tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester = 4:1): light stabilizer (bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate) = 98%: 1.5%: 0.5%; the other layer components are the same as those in Example 2, and the preparation method is the same as that in Example 2.

[0093] Comparative Example 4

[0094] In this embodiment, the core layer 2 contains the following components in percentage by mass: PETG (SKYGREEN, S2012): PA (MXD6) = 60%: 40%, and the other layer components are the same as those in Example 2, and the preparation method is consistent with that in Example 2.

[0095] Comparative Example 5

[0096] In this embodiment, the core layer 2 contains the following components in percentage by mass: PETG (SKYGREEN, S2012): PA (MXD6): antioxidant (tris(2,4-di-tert-butylphenyl)phosphite: pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate=4:1)=58%:40%:2.0%, and the other layer components are the same as those in Example 2, and the preparation method is consistent with that in Example 2.

[0097] Comparative Example 6

[0098] In this embodiment, the core layer 2 contains the following components in percentage by mass: PETG (SKYGREEN, S2012): PA (MXD6): light stabilizer (bis (2,2,6,6-tetramethyl-4-piperidinyl) sebacate) = 58%: 40%: 2.0%, and the other layer components are the same as those in Example 2, and the preparation method is consistent with that in Example 2.

[0099] Comparative Example 7

[0100] In this embodiment, the cast sheet is stretched transversely, and the stretching conditions are adjusted to: the stretching ratio is 2.5 times. The other layer components are the same as those in Example 2, and the preparation method is consistent with that in Example 2.

[0101] Comparative Example 8

[0102] In this embodiment, the cast sheet is longitudinally stretched, and the stretching conditions are adjusted to: the stretching ratio is 1.0 times. The other layer components are the same as those in Example 2, and the preparation method is consistent with that in Example 2.

[0103] The thickness, tensile strength, heat sealing temperature and strength, elongation at break, water vapor permeability, shrinkage, haze, transparency, light transmittance, oxygen permeability and aging resistance of the encapsulated aging-resistant PETG shrink films prepared in Examples 1 to 5 and Comparative Examples 1 to 7 were tested respectively, wherein the tensile strength and elongation at break were tested according to the GB / T 1040.3 method, the heat sealing performance was tested according to the BMSTTO1 method, the light transmittance and haze were tested according to the relevant methods of GB / T 2410-2008, the oxygen permeability and the like were tested according to the relevant methods of ASRM, the wetting tension and the like were tested according to the relevant methods of GB / T 14216-2008 / 1S0 8296: 2003, the aging resistance test conditions were tested according to GB / T 16422.2-1999, the aging box was set at a temperature of 60°C, a humidity of 60%, and the irradiance of the light source with a wavelength between 290 and 800 nm was selected to be 550 W / m2. The results are shown in Table 1.

[0104] Table 1 Performance of aging-resistant PETG packaging shrink film

[0105] As can be seen from Table 1, by comparing Implementation Cases 1 to 5, when the content of functional masterbatch used in the surface layer increases, its wetting tension increases, but its haze, transparency and light transmittance decrease. The PA content in the core layer can effectively improve the barrier properties of the film, but the shrinkage rate of the film will decrease.

[0106] When the modified PET used in the surface layer is YH101 (Comparative Example 1), its heat sealing strength is reduced and the heat sealing temperature needs to be increased to 135°C.

[0107] When the core layer is PA and additives and does not contain PETG (Comparative Example 2), the film basically loses its shrinkage, and its tensile strength and elongation at break are significantly reduced, and its moisture permeability is relatively large, which is much lower than that of Implementation Case 2.

[0108] When the core layer is PETG and additives and does not contain PA (Comparative Example 3), the water vapor permeability and oxygen permeability of the film are high, and the barrier property is significantly reduced.

[0109] When the core layer does not contain antioxidants and light stabilizers, or contains only one of them (Comparative Examples 4 to 6), the aging resistance of the film is poor, which is quite different from the examples.

[0110] When the process stretching ratio is not appropriately selected (Comparative Example 7), the film has a low degree of crystalline orientation, low oxygen and moisture barrier properties, and poor shrinkage. When uniaxial stretching is used (Comparative Example 8), the film's transverse orientation and crystallinity are too high, resulting in reduced transparency and light transmittance of the film.

[0111] The above examples are merely illustrative of the present invention and do not constitute a limitation on the protection scope of the present invention. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation on the present invention. In addition, the technical features involved in the various embodiments of the present invention described above can be combined with each other as long as they do not conflict with each other. In addition, the above are only some embodiments of the present invention, not all embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the technical field without making creative work belong to the scope of protection of the present invention.

Claims

1. An aging-resistant PETG shrink film for protecting thin-film solar cells, characterized in that: The shrink film layer structure is a three-layer structure of A / B / A; wherein the raw materials of the A layer include PET modified with NPG and a functional masterbatch; the raw materials of the B layer include PA, PETG, an antioxidant and a light stabilizer; The A layer contains the following components by mass percentage: NPG modified PET: functional masterbatch = 99.2~96.0%: 0.8~4.0%; The B layer contains the following components by mass percentage: PETG: PA: antioxidant and light stabilizer = 48-69.4%: 30-50%: 0.6-2.0%; The NPG-modified PET is Huahong Chemical Fiber WS501Y; The functional masterbatch is a compound of at least one of silicon dioxide, talcum powder, clay and kaolin and at least one of oleic acid amide and fenic acid amide.

2. The aging-resistant PETG shrink film for protecting thin-film solar cells according to claim 1, characterized in that: The PETG is at least one of SKYGREEN® S2012, Eastman GN071 or Eastman 0603.

3. The aging-resistant PETG shrink film for protecting thin-film solar cells according to claim 1, characterized in that: The PA is at least one of MXD6 and Grivory G21.

4. The aging-resistant PETG shrink film for protecting thin-film solar cells according to claim 1, characterized in that: The antioxidants are tris(2,4-di-tert-butylphenyl)phosphite and pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

5. The aging-resistant PETG shrink film for protecting thin-film solar cells according to claim 1, characterized in that: The light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

6. A method for preparing an aging-resistant PETG shrink film for protecting thin-film solar cells according to any one of claims 1 to 5, characterized in that: The steps include: (1) The raw materials are uniformly mixed in a planetary mixer according to the proportion and then dried, and melt-plasticized in the corresponding extruder according to the mixing of the core layer and the surface layer; (2) Setting the three-layer structure of ABA, the melt is extruded through the same die head with a temperature of 260-280°C, and the cast sheet is cooled and formed on a quenching roller; (3) longitudinally stretching the cast sheet under the following conditions: preheating at 80-90°C, stretching the sheet at 80-100°C to a ratio of 1-2 times, and cooling the sheet at 40-60°C after longitudinal stretching; (4) Performing a transverse stretching operation, the stretching conditions are: preheating at 90-110°C, stretching the film to a ratio of 3 to 4 times at 70-90°C, and cooling and shaping the film at 60-80°C after transverse stretching; (5) Pulling and rolling to obtain an aging-resistant heat-retractable thin-film solar cell packaging film.

7. The method for preparing the aging-resistant PETG shrink film for protecting thin-film solar cells according to claim 6, characterized in that: The thickness of the aging-resistant heat-shrinkable thin-film solar cell packaging film is 30 to 100 μm.

Citation Information

Patent Citations

  • Multilayer oriented film

    CN101374658A

  • Layered composite EVA film for low shrinkage solar cell encapsulation

    CN102285175A